How do Higher Education Students manage their Digital Footprints before Finding a Job? - FehérKatalin (Journal of Education and Vocational Research, 2013)
We have identities and we can communicate online on the internet and in social networks. The question is how we can define and manage social roles/online representations on digital platforms and in social media? â€œDigital identityâ€ is in the focus in this exploratory phase of our research the aim of which has been to map how identity refers to a driver in a digital setting with digital footprints, visibility or nonvisibility, professionalism and privacy in online publicity. Our empirical research has been trying to explore this phenomenon of the digital media for online personal strategy with segmentation. The first exploratory phase focused on the studentsâ€™ segment prior to initial employment. We were wondering which points of decision were relevant in digital identity strategy for them and how they would replace their strategy consciously prior to employment. We had a qualitative research with semi-structured interviews. Our results show that digital identity phenomena define social roles/online strategies and representations on digital platforms and in social media. Members of the research segment have some strategies to manage their digital footprints. They would like to change their profile from â€œstudentâ€ to that of a â€œprofessionalâ€ assuming less activity in digital context.